A MoS2 and Graphene Alternately Stacking van der Waals Heterostructure for Li+/Mg2+ Co‐Intercalation. (21st July 2021) - Yu, Xianbo; Zhao, Guangyu; Liu, Chao; Wu, Canlong; Huang, Huihuang; He, Junjie; Zhang, Naiqing
Abstract: Owing to the low‐cost, dendrite‐free formation, and high volumetric capacity, rechargeable Li + /Mg 2+ hybrid‐ion batteries (LMIBs) have attracted great attention and are regarded as promising energy storage devices. However, due to the strong Coulombic interaction of Mg 2+ with host materials, the traditional "Daniell Type" LMIBs with only Li + intercalation usually cannot ensure a satisfactory energy density. Herein, graphene monolayers are arranged intercalating into MoS2 interlamination to construct van der Waals heterostructures (MoS2 /G VH). This operation transforms the construction of ion channels from pristine interlamination of two MoS2 monolayers to the interlamination of MoS2 monolayer with graphene monolayer, thereby greatly reducing ion diffusion energy barriers. Compared with pristine MoS2, the MoS2 /G VH can obviously reduce the migration energy barriers of Li + (from 0.67 to 0.09 eV) and Mg 2+ (from 1.01 to 0.21 eV). Moreover, it is also demonstrated that MoS2 /G VHs realize Li + /Mg 2+ co‐intercalation even at a rate current of 1000 mA g −1 . As expected, the MoS2 /G VH exhibits superior electrochemical performance with a reversible capacity of 145.8 mAh g −1 at 1000 mA g −1 after 2200 cycles, suggesting the feasibility of potential applications for high‐performance energy storage devices. Abstract : A facile self‐assembly method via electrostatic attraction is applied to prepare MoS2 /graphene van der Waals heterostructures, which can transform the ion channel construction from pristine interlamination of two MoS2 monolayers to the interlaminatiof the MoS2 monolayer with the graphene monolayer, thereby reducing the diffusion energy barrier of ions in favor of introducing Li + /Mg 2+ co‐intercalation into the host material.